CLINICAL PHARMACOLOGICAL APPROACH TO THE RATIONAL TREATMENT OF INFECTIOUS DISEASES (World Bulletin of Public Health, 2024)
The article summarizes the literature data on therapeutic nutrition, including that of infectious patients. The variants of diets according to Pevzner are given in accordance with the variants of standard diets used in the treatment of infectious patients. A brief description of artificial therapeutic nutrition in the therapy of patients with various infectious diseases is given. Particular importance is given to the scientific substantiation of therapeutic nutrition in the complex therapy and rehabilitation of infectious patients. The correct choice of therapeutic nutrition contributes to the normalization of lost functions and the fastest possible restoration of the human body after an infectious disease.
Keywords: Therapeutic nutrition; method; treatment